The Effectiveness of Canva-Based IPAS Learning Media on Elementary School Students' Learning Motivation - Triyono Triyono; Sarwi Sarwi; Cepi Kurniawan (Proceedings of International Conference on Science, Education, and Technology, 2026)
This study examined the effectiveness of Canva-based Natural and Social Sciences (IPAS) learning media in enhancing elementary school students’ learning motivation. A pre-experimental one-group pretest-posttest design was implemented at SD Negeri Karangmalang involving 15 students selected through saturated sampling. Data were collected through observation, documentation, and a four-point Likert-scale learning motivation questionnaire. Descriptive statistics were used to summarize students’ motivation scores, while inferential analysis included the Shapiro-Wilk normality test and paired-samples t-test. The mean motivation score increased from 63.87 in the pretest, categorized as sufficient, to 84.40 in the posttest, categorized as very good. The pretest and posttest scores were normally distributed, with p-values of 0.200 and 0.167, respectively. The paired-samples t-test indicated a statistically significant improvement in students’ learning motivation after the implementation of Canva-based IPAS learning media, t (14) = -11.284, p < 0.001, with a large within-subject effect size (Cohen’s dz = 2.91). Classroom observations further indicated improvements in students’ attention, enthusiasm, and participation during IPAS learning. These findings suggest that visually structured and interactive Canva-based media can support motivational engagement in elementary IPAS classrooms. However, because this study involved a small sample and did not include a control group, further research using a more rigorous comparative design is recommended.